DATA-BASED EDUCATION FINANCING MANAGEMENT: A STRATEGY TO IMPROVE PRIORITY INDICATOR ACHIEVEMENT IN ELEMENTARY SCHOOLS - siti munawaroh; ngurah ayu nyoman murniati; Supandi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The low literacy and numeracy scores on the Education Report Card (Report Card) have prompted the urgency of precise financial governance. This study aims to analyze data-driven financing management strategies to improve priority indicators at SDN 5 Godong. Using a qualitative case study method, data was collected from eight informants (the Principal, Treasurer, Teachers, School Committee, and parents) through interviews, observations, and document review. Data validity was ensured through triangulation of sources and techniques. The results indicate that integrating the ARKAS (School Budget Alignment) with the Education Report Card (Report Card) increased the efficiency of instructional allocation by 15%. The findings identified the